Farming in the shadows of Rome: A multi‐proxy palaeoenvironmental record from Loch Clunie—Perthshire - Samantha E. Jones; Maarten Blaauw; Fraser Hunter; Olalla López‐Costas; Antonio Martínez Cortizas; Tim M. Mighall; Gordon Noble (Journal of Quaternary Science, 2026)
Roman impacts on local society is a subject of international significance. Loch Clunie, Perthshire, lies only 5.4 km from Inchtuthil, the only Roman legionary fortress in Scotland, and contains two crannogs and a probable lakeside hillfort. Despite this proximity and the likelihood of local–Roman interaction, these sites remain unexcavated. This paper presents palaeoenvironmental evidence for long‐term social‐economic change at Loch Clunie, contributing to a region with few well‐dated environmental–archaeological sequences for the Roman Iron Age and beyond. Pollen, non‐pollen palynomorph and sedimentological analyses are used to investigate patterns of environmental change and social activity from the later prehistoric period through to the late medieval era. The results indicate the presence of a local farming community pre‐dating Roman incursions into Scotland. This is followed by a marked increase in barley cultivation either slightly before or during the early Roman Iron Age. The mid‐Roman Iron Age is represented by a short‐lived vegetation downturn and subsequent recovery. However, the most distinct change occurs during the late Roman Iron Age, represented by a pronounced decline to almost complete disappearance of barley from the third to fourth centuries AD, lasting approximately 400 years. Settlement–economic downturns are emerging at other sites in north‐eastern Scotland with comparable temporal scales, although their causes appear to be complex. At Loch Clunie, there is no evidence to link this event to the Severan campaigns of AD 208–211. Indeed, this event appears slightly later. There is evidence, however, for a rise in lake levels, which could potentially be linked to Late Roman climatic deterioration.

A case report of a pathology in the ‘whip’ of a flagellicaudatan sauropod - Tom T.P. van der Linden; D. Ray Wilhite; Gunnar T. Bivens; D. Cary Woodruff; Rick J. Hunter; Tim Stecko; Brian D. Curtice (The Science of Nature, 2026)
Flagellicaudatan sauropods are well known for their elongated tails which end in a ‘whiplash’-like structure, consisting of biconvex rod-like caudal vertebrae lacking a neural arch. A remarkably well-preserved and relatively complete specimen of Barosaurus from the Upper Jurassic Morrison Formation preserves a number of these vertebrae, including the last two that terminate the axial series. The penultimate element preserves a distinct callus which we investigated, together with the terminal caudal vertebra, using X-ray computed tomography. A transverse fracture initiated the formation of the callus, highlighted by extensive, disorganized vascularization of the bone outside of the cortex. Healing was likely still ongoing as the vertebra remains in two parts. Although various etiologies can be proposed for the trauma, none can be unambiguously put forward as the cause. The last caudal shows an interesting vascular pattern, and together with the lack of a posterior articular surface, can here be definitely identified as the last vertebra in the axial series. There is substantial variability in the morphology of the last caudal vertebra throughout Sauropoda, and future studies should focus on the soft tissues in this part of the tail, thereby enlightening the potential function of the ‘whip’. We also highlight here the use of high-resolution scanning to reveal the internal structures of fossils in detail when consumptive analysis is not possible.

The EGS Collab project: Outcomes and lessons learned from hydraulic fracture stimulations in crystalline rock at 1.25 and 1.5 km depth - Tim Kneafsey; Pat Dobson; Doug Blankenship; Paul Schwering; Mark White; Joseph P. Morris; Lianjie Huang; Tim Johnson; Jeff Burghardt; Earl Mattson; Ghanashyam Neupane; Chris Strickland; et al. (Geothermics, 2025)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Soil moisture increases stability of North American Pinus species growing in sandy soils - Jeffery B. Cannon; S. Hunter Scully; R. Scott Taylor; Chris J. Peterson; Tim Newson (Forest Ecology and Management, 2024)

Economic evaluations of urban green and blue space interventions: A scoping review - Christopher Tate; Ngan Tran; Alberto Longo; John Barry; Tim Taylor; Ciaran O'Neill; Ruth Hunter (Ecological Economics, 2024)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Potential establishment and ecological effects of bighead and silver carp in a productive embayment of the Laurentian Great Lakes - Lori N. Ivan; Doran M. Mason; Hongyan Zhang; Edward S. Rutherford; Tim Hunter; Shaye Sable; Aaron T. Adamack; Kenneth Rose (Biological Invasions, 2020)
Bighead carp H . nobilis and silver carp Hypothalmichthys molitrix (collectively bigheaded carps, BHC) are invasive planktivorous fishes that threaten to enter the Laurentian Great Lakes and disrupt food webs. To assess the likelihood of BHC establishment and their likely effects on the food web of Saginaw Bay, Lake Huron, we developed a multi-species individual-based bioenergetics model that tracks individual bighead and silver carp, four key fish species, and seven prey biomass groups over 50 years. The model tracks the daily consumption, mortality and growth of all individuals and the biomass dynamics of interacting prey pools. We ran simulation scenarios to determine the likelihood of BHC establishment under initial introductions from 5 to 1 million yearling and older individuals, and assuming variable age-0 carp survival rates (high, intermediate, and low). We bounded the survival of age-0 BHC as recruitment continues to be one of the biggest unknowns. We also simulated the potential effects of an established population of 1 million bighead carp or silver carp assuming variation in age-0 survival. Results indicated that as few as 10 BHC could establish a population assuming high or intermediate age-0 survival, but at least 100,000 individuals were needed to establish a population assuming low age-0 survival. BHC had negative effects on plankton and planktivorous fish biomass, which increased with BHC density. However, piscivorous walleye Sander vitreus appeared to benefit from BHC establishment. The potential for BHC to establish and affect ecologically and economically important fish species in Saginaw Bay is a cause for concern.

Optimizing treatment outcome of first-line anti-tuberculosis drugs: the role of therapeutic drug monitoring - Roger K. Verbeeck; Gunar Günther; Dan Kibuule; Christian Hunter; Tim W. Rennie (European Journal of Clinical Pharmacology, 2016)

European policy responses to climate change: progress on mainstreaming emissions reduction and adaptation - Frans Berkhout; Laurens M. Bouwer; Joanne Bayer; Maha Bouzid; Mar Cabeza; Susanne Hanger; Andries Hof; Paul Hunter; Laura Meller; Anthony Patt; Benjamin Pfluger; Tim Rayner; et al. (Regional Environmental Change, 2015)

Regional differentiation among populations of the Diamondback terrapin (Malaclemys terrapin) - Kristen M. Hart; Margaret E. Hunter; Tim L. King (Conservation Genetics, 2014)

Variation in microbial communities colonizing horticultural slow sand filter beds: implications for filter function - Paul J. Hunter; Leo A. Calvo-Bado; Nick R. Parsons; Tim R. Pettitt; Geoff M. Petch; Eve Shaw; J. Alun W. Morgan; John M. Whipps (Irrigation Science, 2013)

Oil pollution and climate have wide‐scale impacts on seabird demographics - Stephen C. Votier; Ben J. Hatchwell; Andrew Beckerman; Robin H. McCleery; Fiona M. Hunter; Jayne Pellatt; Mark Trinder; Tim R. Birkhead (Ecology Letters, 2005)
Oil spills often spell disaster for marine birds caught in slicks. However, the impact of oil pollution on seabird population parameters is poorly known because oil spills usually occur in wintering areas remote from breeding colonies where birds may be distributed over a wide area, and because it is difficult to separate the effects of oil pollution from the effect of natural environmental variation on seabird populations. Using a long‐term data set we show that over‐winter survival of adult common guillemots ( Uria aalge ) is negatively affected by both the incidence of four major oil‐spills in their wintering grounds and high values of the North Atlantic Oscillation (NAO) index. After controlling for the effect of the NAO index, we show that winter mortality of adult guillemots is doubled by major oil pollution incidents. Our results demonstrate that oil pollution can have wide‐scale impacts on marine ecosystems that can be quantified using populations of marked individuals to estimate survival.